Excitation spectra and electromagnetic transitions between low-lying nonrotational states of odd-proton nuclei with Z = 97−109; Physical Review C; Vol. 108 - Iss. 4 - Malov L. A. Leonard Aleksandrovich; Bezbakh A. N. Anna Nikolaevna; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Jolos R. V. Rostislav Vladimirovich (2023, 2023)
Background: Calculations of the structure of the low-lying states of nuclei with Z = 97–109 play an important role in understanding the properties of nuclei belonging to the new region of the nuclide chart, which is available now for experimental study. Purpose: To calculate quasiparticle-phonon structure and the reduced γ -transition probabilities for the excited states with excitation energies below 1 MeV for odd-proton nuclei with Z = 97−109. Methods: The quasiparticle-phonon model, which takes into account the quasiparticle-phonon interaction of different multipolarities, is used as a basis for the calculations. Results: The quasiparticle-phonon structure and the γ -reduced transition probabilities of odd-proton nuclei 263,265,267,269Mt, 259,261,263,265Bh, 255,257,259,261,263Db, 251,253,255,257,259,261Lr, 249,251,253,255Md, 245,247,249,251Es, and 243,245,247Bk are calculated. The α-decay chains starting from 263,265,267,269Mt are analyzed. Conclusion: The structure of the nuclear states with excitation energies below 1 MeV in the considered nuclei is mainly exhausted by the one-quasiparticle component. However, in some isotopes the quasiparticle-phonon admixtures plays an important role to destroy the smooth isotopic dependence of energy of the states. The nuclei in the α-decay chains starting from 263,265,267,269Mt have up to two α-decay lines. The number of α-decay lines could be different in the α-decay chain and in the direct production of the nucleus.